Qualidade da água para irrigação na microbacia do Coqueiro, Estado de São Paulo - Franco, Renato A.M. [UNESP]; Hernandez, Fernando B.T. [UNESP] (FapUNIFESP (SciELO), 2009)
The aim of this study was to evaluate the physico chemical characteristics of water quality for irrigation purposes in the micro basin of Coqueiro, a tributary on the right bank of the São José dos Dourados river, located between the municipalities of Jales, São Francisco, Palmeira d'Oeste and Dirce Reis, in the state of São Paulo, Brazil. Water samples were collected at five geo-referenced points along the stocam and analysed monthly for one year. The parameters analysed were: suspended and dissolved solids, turbidity, electrical conductivity, pH, calcium, magnesium, hardness and total iron. The result showed that the physico chemical parameters had the classification of medium potential for damage to the irrigation system, except total iron, which was classified as having medium to high potential for damage by clogging for localized irrigation systems.
Water quality for irrigation in the micro watershed of the Coqueiro stream, São Paulo State, Brazil
Keywords: Management; Silting; Watershed; Dirce